Perlindungan Hukum terhadap Hak Anak Incest Berdasarkan Hukum Negara Indonesia - Rindi Putri Afifah; Nindya Prasetya Wardhani; Aura Shava Dhinda Salsabila (Jurnal Hukum Lex Generalis, 2021)
Marriage is a man's bond with a woman as a husband and wife to form a happy and eternal family. Marriage can be said to be valid or invalid depending on the or unfulfillment of the conditions of marriage stipulated in Article 6 to Article 12 of the Marriage Act. However, among the articles, Article 8 also mentions marriage that is prohibited, one of which is due to blood relations in the lineage. The marriage is called incest. The problem in Indonesia is that there are people who perform such incestuous marriages and what if in the marriage is born a child. Therefore, people must be aware of the legal protection of incest children's rights under Indonesian law.